Does Economic Sanction Work? The Case of North Korea - Jinhwan Oh (European Regional Science Association (ERSA), 2010)
Based on the gravity model of international trade, this paper initially analyzes North Korea's international trade pattern, which tends to follow the prediction of the gravity model: a positive relationship between trade and trading partners' GDP, and negative relationship between trade and distance. This pattern has been consistently preserved over recent several years in spite of economic sanctions by various countries, implying that those sanctions do not significantly change North Korea's trade environment. This result lies on the substitutability of goods among countries. For example, North Korea has traded increasingly larger amount of goods with China and Korea since Japan imposed sanctions against Pyeongyang. Unless all countries strictly agree on imposing sanctions against a specific country, which is almost impossible to be realized, imposing economic sanction will turn out to be unsuccessful.
Keywords: F15; F51; R10; R40; 330; International Trade; Gravity Model; Economic Sanctions; North Korea